Avaliação de fatores neurotróficos e marcadores imunológicos em indivíduos com transtorno bipolar - Izabela Guimaraes Barbosa (2012)
Introduction: Bipolar disorder (BD) is a prevalent and chronic illness associated with substantial morbidity. There is a growing body of evidence indicating that disturbance at neurotrophic factors and immunologic parameters play an important role in the pathophysiology of BD. Objective: The aim of this study was to evaluate the plasma levels of different neurotrophic factors (BDNF, NGF and GDNF) and immunologic parameters (TNF-, sTNFR1, sTNFR2, adiponectin, leptin, resistin, and the chemokines CCL2, CCL3, CCL11, CCL24, CXCL8 and CXCL10), and evaluate the frequency of leucocytes and patways activated by neurotrophic factors and immunologic parameters in BD patients in different mood state in comparison with controls. Methods: 93 BD type I patients and 58 controls matched by age, gender and education level were enrolled in this study. All subjects were assessed by the Mini-International Neuropsychiatry Interview and the patients were also evaluated by the Young Mania Rating Scale and the Hamilton Depression Rating Scale. The plasma levels of BDNF, NGF, GDNF, TNF- and its soluble receptors (sTNFR1 and sTNFR2), adipokines, and several chemokines were measured by ELISA. The frequency of leucocytes and activated pathways of NF-B (p65) and MAPKs (ERK1/2 and p38) was measured by FACS. The activaction of MAPK pathway (ERK1/2 and p38) and NF-B (p65) pathway was measured by Western blotwith proteic extracts. Results: BD patients presented higher plasma levels of GDNF and BDNF and lower plasma levels of NGF in comparison with controls. Regarding immunologic parameters, BD patients showed higher plasma levels of sTNFR1, adipokines (mainly adiponectin and leptin), and CCL11, CCL24, and CXCL10. BD patients presented lower plasma levels of CXCL8 in comparison with controls. BD patients presented increased frequency of monocytes (CD14+) and lower frequency levels of T regulatory lymphocytes (CD4+CD25+FOXp3+). Moreover, BD patients presented increased phosphorylation levels of NF-B/p65, p38 and ERK1/2. Conclusions: The present study reinforces the view that BD is associated with neurotrophic factors and immune parameters imbalance.